Characteristics of mobile learning environments in developing countries - Imtinan, Umera; Chang, Vanessa; Issa, Tomayess (Common ground publishing com, 2012)
This paper examines and reviews the current literature on mobile learning in developing countries. Mobile device is becoming a more popular interface for connecting with the world and mode of digital presence than the desktop computing devices. Mobile technologies in the developing world enable people to connect to the Internet, become more conversant with the digital world, and network globally via social networking forums. Mobile technologies in developing countries such as India, Indonesia, Pakistan, Kenya and South Africa have significantly increased and advanced. In spite of limited Information and Communications Technology (ICT) resources and an unstable infrastructure, good telecom services exist in the form of cellular networks which provide a favourable environment for mobile learning. The literature suggests that there is pervasive use of mobile devices that would facilitate the uptake of mobile learning in developing countries. However, few researchers have looked into the potential use of mobile devices in learning environments in developing countries. To ascertain the extent of mobile leaning in developing countries, this paper examines the current literature on mobile learning research in developing countries including projects, implementations, theories and conceptualizations of mobile learning for these countries.